ANALISIS META PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN - Merisman, Merisman; Nasution, Fitrah Panabari; Hoiriah, Hoiriah; Indriani, Riri; Elyanis, Rafidah; Zaitul, Zaitul (Gapenas Publisher, 2025)
This study aims to quantitatively examine the effect of organizational culture on employee performance through a meta-analysis of 39 studies published between 2020 and 2025. Data were collected from national and international journals using predefined inclusion and exclusion criteria. A random-effects model was employed to accommodate heterogeneity across studies. The results reveal a positive and statistically significant relationship between organizational culture and employee performance, with a combined effect size of 0.122 (p < 0.001), categorized as small to moderate based on Cohen’s classification. Egger’s regression test and Trim-and-Fill analysis indicate no significant publication bias, supporting the validity of the findings. This study underscores the importance of developing adaptive, participatory, and communicative organizational cultures as strategic efforts to enhance human resource performance. The findings contribute both theoretically and practically to the field of management, particularly in strengthening organizational culture as a key determinant of performance.